EMOTIONAL INTELLIGENCE AND WORK STRESS ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION - Prasetyo, Sulaksono; Rahayu, Sri; Sari, Anita Kartika (Journal Informatic, Education and Management (JIEM), 2026)
This study investigated the effects of emotional intelligence and work stress on employee performance through job satisfaction at the Class III Port Authority of Tanjung Pakis, Indonesia. Using a quantitative approach and PLS-SEM analysis, the findings showed that emotional intelligence, work stress, and job satisfaction positively influenced employee performance. However, emotional intelligence and work stress did not significantly affect job satisfaction, indicating that job satisfaction did not mediate the relationships between these variables and employee performance. The findings contribute to the Job Demands-Resources and Conservation of Resources theories, particularly in the context of Indonesia’s public maritime sector. The study recommends human resource strategies that focus on enhancing emotional competencies, optimizing productive levels of work stress, and implementing separate job satisfaction improvement initiatives to strengthen employee performance.